Tourism and Crisis: Comparing the Impacts of COVID-19 and Natural Disasters on The Hajj and Umrah Industry - Supriadi, Udin (The international journal of religious tourism and pilgrimage, 2022)
This study aims to compare the impact of the Covid-19 Pandemic and Natural Disasters on the Hajj and Umrah industries. This pilgrimage substantially contributes to foreign exchange earnings; therefore, the negative potential caused by disasters must be a significant concern for policymakers in this sector. In recent years, religious-based tourism, especially the hajj and umrah (the out-of-season pilgrimage to Mecca), has experienced significant rise of demand worldwide. To explore the impact of various disasters on this industry, using the purposive sampling method, semi-structured interviews were conducted with travel agents in Bandung over the course of two months. The findings from this research are that there is a sharp difference in the destructive impact of the Covid-19 Pandemic when compared to natural disasters. In both instances, the companies suffered from external and internal pressures. The internal problems are the loss of revenue while they still need to pay employee salaries, customers’ demands for refunds, and the uncertainty whether they could re-open their business. Meanwhile, externally, they have been faced with strict regulations on health protocols, the weakening global economy, increased operational costs, and ever-changing policies made by the governments of Indonesia and Saudi Arabia.